Konsep Jihad dalam Alquran dan Aktualisasinya dalam Pendidikan - Husni, Husni (TAJDID, 2020)
This article seeks to elaborate on the meaning of jihad in the Koran and its actualization in education. This research uses the content analysis method. Through a critical study of jihad’s meaning in the Koran, this study concludes that Islamic teachings love peace among human beings and do not want hostility and violence, let alone a war. In Islam, peace is not only for Muslims themselves but for humans even though when Muslims are attacked, every Muslim is obliged to defend himself in order to realize jihad fi sabi li llah. Therefore, jihad also means keeping peace not disturbed by intruders. The actualization of jihad in education refers to three educational foundations, ontological, epistemological, and axiological foundations